2016
DOI: 10.1097/yco.0000000000000216
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based cognitive therapy for residual depressive symptoms and relapse prophylaxis

Abstract: Purpose of review This article reviews the recent evidence for mindfulness based cognitive therapy (MBCT) for patients with residual depressive symptoms or in remitted patients at increased risk for relapse. Recent findings Randomized controlled trials have shifted focus from comparing MBCT with treatment-as-usual to comparing MBCT against interventions. These studies have provided evidence for the efficacy of MBCT on par with maintenance antidepressant pharmacotherapy and leading to a relative reduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 36 publications
(45 reference statements)
2
15
0
2
Order By: Relevance
“…a strategy for increasing perceived and behavioral control over stress, pain, depression, and other stress-related conditions (41,42). Along with stress-related VmPFC plasticity, we found the ventral striatum to increase during late relative to early runs in the stress versus neutral contrast, consistent with its role in avoidant learning and motivation (43,44).…”
Section: Discussionsupporting
confidence: 59%
“…a strategy for increasing perceived and behavioral control over stress, pain, depression, and other stress-related conditions (41,42). Along with stress-related VmPFC plasticity, we found the ventral striatum to increase during late relative to early runs in the stress versus neutral contrast, consistent with its role in avoidant learning and motivation (43,44).…”
Section: Discussionsupporting
confidence: 59%
“…A recent systematic review of meditative movement practices found significant impact on depression severity (Zou et al, 2018). The therapeutic effects of meditative movement on affective disorders, such as depression and anxiety, seem to be related to the cultivation of awareness of internal bodily sensations (i.e., body awareness; Payne and Crane-Godreau, 2013), similar to findings with standard seated meditation studies (Segal et al, 2010;Segal and Walsh, 2016). Recent studies have begun to identify important subjective and physiological aspects of this body-awareness mechanism that are particularly relevant to an improved sense of vitality in MDD (Payne and Crane-Godreau, 2013).…”
Section: Introductionmentioning
confidence: 61%
“…It was originally developed to prevent depression relapse [25][26][27] and has been modified to address a variety of chronically painful conditions. It was originally developed to prevent depression relapse [25][26][27] and has been modified to address a variety of chronically painful conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Mindfulness-Based Cognitive Therapy (MBCT) teaches mindfulness meditation and cognitivebehavioral coping skills and directly applies these skills to address disease-related cognitions and coping. It was originally developed to prevent depression relapse [25][26][27] and has been modified to address a variety of chronically painful conditions. 28 MBCT targets maladaptive disease-related beliefs in addition to stress reduction and is traditionally delivered using a group format with groups of 8-10 individuals.…”
Section: Introductionmentioning
confidence: 99%